2015
DOI: 10.1038/srep10224
|View full text |Cite
|
Sign up to set email alerts
|

CART treatment improves memory and synaptic structure in APP/PS1 mice

Abstract: Major characteristics of Alzheimer’s disease (AD) include deposits of β-amyloid (Aβ) peptide in the brain, loss of synapses, and cognitive dysfunction. Cocaine- and amphetamine-regulated transcript (CART) has recently been reported to attenuate Aβ-induced toxicity. In this study, CART localization in APP/PS1 mice was characterized and the protective effects of exogenous CART treatment were examined. Compared to age-matched wild type mice, 8-month-old APP/PS1 mice had significantly greater CART immunoreactivity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 37 publications
2
26
0
Order By: Relevance
“…Therefore, in the present study, we also investigated the efficacy of TRF to preserve recognition memory in AβPP/PS1 mice using a spontaneous behavioral response (exploration of novel objects) that does not require stimulus presentation [47]. Our results demonstrated that the AβPP/PS1 mice supplemented daily with water showed a significant decline in novel object exploration time compared with aged-matched WT, consistent with other age-related memory impairment in AβPP/PS1 mice [48–50]. This decline in cognitive function was rescued to a greater extent by daily TRF supplementation than by PO, suggesting TRF is the active antifibrillogenic and neuroprotective component.…”
Section: Discussionsupporting
confidence: 67%
“…Therefore, in the present study, we also investigated the efficacy of TRF to preserve recognition memory in AβPP/PS1 mice using a spontaneous behavioral response (exploration of novel objects) that does not require stimulus presentation [47]. Our results demonstrated that the AβPP/PS1 mice supplemented daily with water showed a significant decline in novel object exploration time compared with aged-matched WT, consistent with other age-related memory impairment in AβPP/PS1 mice [48–50]. This decline in cognitive function was rescued to a greater extent by daily TRF supplementation than by PO, suggesting TRF is the active antifibrillogenic and neuroprotective component.…”
Section: Discussionsupporting
confidence: 67%
“…Not only that, Cocaine-and amphetamine-regulated transcript (Exogenous CART treatment) in APP/PS1 mice has obstructed depolarization of the mitochondrial membrane and provoke mitochondrial complex, I and II activities, thereby leading to an increase in ATP levels. Further, CART treatment also reduces ROS and 4-HNE level that mitigate oxidative DNA damage in AD brain [186]. In case of PD, MicroRNA-7 (miR-7) has been found to elicit a protective role in cellular models of PD.…”
Section: Methazolamide (Mtz)mentioning
confidence: 99%
“…; Jin et al. ), respectively mimicking the preclinical, early and early to middle stages of AD (Jiang et al. ).…”
Section: Resultsmentioning
confidence: 99%
“…Abnormal SAP102 expression in the hippocampal subregions of APP/PS1 mice In the past decade, because of their early onset of pathological alterations and stable genetic background, APP/PS1 mice have become a very popular AD mouse model (Radde et al 2006;Bilkei-Gorzo, 2014). The APPswe/PS1dE9 double-transgenic mice used in this study develop amyloid plaques at 4 months, and the number of plaques increases with age (Garcia-Alloza et al 2006;Ruan et al 2009;Malm et al 2011;Edwards et al 2014;Jin et al 2015;Kelly et al 2017). Therefore, to investigate and compare dynamic changes in SAP102 expression in the hippocampal subregions, we chose APP/PS1 mice at the time points of 2 months (no plaques; Savonenko et al 2005 We first observed SAP102 expression in WT mice, and the trends were generally the same as those in age-matched rats; the SAP102 fluorescence intensities in the hippocampal subfields of WT mice increased slightly from 2 to 7 months of age (Fig.…”
Section: Sap102 Maintained Higher Levels In the Rat Hippocampal Dg Anmentioning
confidence: 97%